Half-Century Changes in LULC and Fire in Two Iberian Inner Mountain Areas - Catarina Romão Sequeira; Francisco Castro Rego; Cristina Montiel-Molina; Penelope Morgan (Fire, 2019)
Wildfires in the Iberian Peninsula were large and frequent in the second half of the 20th century. Land use and land cover (LULC) also changed greatly. Our aim was to understand the relationship between LULC and fire in the western and eastern ends of the Iberian Central Mountain System. We compared two case study landscapes, the Estrela massif and the Ayllón massif, which are biophysically similar but with different social-ecological contexts. In both, fires were in general more likely in shrublands and pastures than in forests. Shrublands replaced forests after fires. Contrasting LULC in the two massifs, particularly pastures, likely explained the differences in fire occurrence, and reflected different regional land use policies and history. Fire here is a social-ecological system, influenced by specific LULC and with implications from landscape to regional scales. Understanding how LULC changes interact with fire is powerful for improving landscape and regional planning.